A study on the factors that influencing customer satisfaction towards Melaka Crocodile Farm / Nur Aliya Mohd Fuad , Siti Nasuha Zainudin and Maryam Aziz - Mohd Fuad, Nur Aliya; Zainudin, Siti Nasuha; Aziz, Maryam (Faculty of Hotel and Tourism Management, 2013)
One of the major income generators to Malaysia's economy is through tourism industry. Due to the offerings of tourism industry which is service, it is significant for service provider to emphasize on customer satisfaction towards service quality and prevention of low customer satisfaction to maintain the tourism industry reputation. The purpose of this study is to assess the customer satisfaction towards service quality provided by Melaka Crocodile Farm as well as pointing on the issues in service quality that service provider need to be aware of to reach and exceed customer expectations. Service perform in a service provider may not be visible but can bring a great threat to the service provider by imprinting negative perception and bad customer satisfaction on the overall service quality of the Melaka Crocodile Farm. Therefore, this research is to find out the connection between factors influencing customer to visit Melaka Crocodile Farm with their satisfaction. A total of 50 respondents consisting of Malaysian people are been interviewed. PSPP has been employed for data analysis with all the Cronbach Alphas above 0.7 and all had been fulfilled. The results showed that the service provider is found to have positive influence towards the service quality of Melaka Crocodile Farm. In conclusion, this study provides empirical evidence of service provider offered by the Melaka Crocodile Farm will lead to building of good service quality.